2016
DOI: 10.1002/lary.26018
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of saliva collection to detect pepsin in patients with laryngopharyngeal reflux

Abstract: 3b Laryngoscope, 126:2770-2773, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 26 publications
7
71
2
1
Order By: Relevance
“…Indeed, a sensitive immunoassay for pepsin previously demonstrated up to 100% sensitivity and 89% specificity for reflux as identified by pH monitoring . Since the introduction of MII‐pH monitoring, more recent work has identified the presence of pepsin in the saliva of many patients with impedance‐confirmed proximal reflux, suggesting a potential role for pepsin in the diagnosis of LPR . Proximal reflux is also suggested as a contributor to rhinologic disease such as chronic rhinosinusitis (CRS), a notion bolstered by literature identifying a high prevalence of reflux in patients with poor outcomes following endoscopic sinus surgery for CRS .…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, a sensitive immunoassay for pepsin previously demonstrated up to 100% sensitivity and 89% specificity for reflux as identified by pH monitoring . Since the introduction of MII‐pH monitoring, more recent work has identified the presence of pepsin in the saliva of many patients with impedance‐confirmed proximal reflux, suggesting a potential role for pepsin in the diagnosis of LPR . Proximal reflux is also suggested as a contributor to rhinologic disease such as chronic rhinosinusitis (CRS), a notion bolstered by literature identifying a high prevalence of reflux in patients with poor outcomes following endoscopic sinus surgery for CRS .…”
Section: Introductionsupporting
confidence: 89%
“…In a study of gastroesophageal reflux disease (GERD) patients, Hayat et al demonstrated that salivary pepsin was significantly more likely to be detected in specimens collected in the postprandial period . More recently, however, Na et al studied a population of patients with proximal reflux confirmed with MII‐pH monitoring and found that salivary pepsin levels were significantly higher upon awakening than after meals or when symptoms occurred . Therefore, the optimal timing for collection of salivary pepsin for the purpose of diagnosing EER remains uncertain.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The higher prevalence of salivary pepsin in the latter adult studies compared with ours may have been because their saliva sampling was timed with symptoms. In a study by Na et al, salivary pepsin concentrations were highest after an overnight fast, before any meals were ingested and without any associated symptoms 33 . In our study, all patients had salivary samples obtained after a 2 hour minimum NPO period.…”
Section: Discussionmentioning
confidence: 93%
“…Pepsins are major proteolytic enzymes present in the gastric juices produced by the gastric chief cells and hence can only occur in saliva as a result of gastric contents reaching the oral cavity [21]. It appears that gastro-oesophageal reflux disease patients have higher [pepsin] saliva than healthy individuals, possibly due to more frequent or larger volumes of refluxate reaching the oral cavity in the disease condition [22,23]. Pepsin therefore seems an ideal, acute biomarker of reflux events and the authors hypothesise that higher concentrations of pepsin will be found in saliva if the intake of carbonated beverages or other "refluxogenic" food items has caused the gastric contents to reach the oral cavity.…”
Section: Introductionmentioning
confidence: 99%